Linear High-Order Distributed Average Consensus Algorithm in Wireless Sensor Networks. (27th June 2010) - Xiong Xiong, Gang Gang; Kishore Kishore, Shalinee Shalinee
Abstract : This paper presents a linear high-order distributed average consensus (DAC) algorithm for wireless sensor networks. The average consensus property and the convergence rate of the high-order DAC algorithm are analyzed. In particular, the convergence rate is determined by the spectral radius of a network topology-dependent matrix. Numerical results indicate that this simple linear high-order DAC algorithm can accelerate the convergence without additional communication overhead and reconfiguration of network topology.